2022
DOI: 10.1002/ctm2.882
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide CRISPR/Cas9 screening for therapeutic targets in NSCLC carrying wild‐type TP53 and receptor tyrosine kinase genes

Abstract: Background Targeted drugs have greatly improved the therapeutic outcome of non‐small cell lung cancer (NSCLC) patients compared with conventional chemotherapy, whereas about one‐third of patients are so far not suitable for targeted therapy due to lack of known driver oncogenes such as a mutated receptor tyrosine kinase (RTK) genes. In this study, we aimed to identify therapeutic targets for this subgroup of NSCLC patients. Methods We performed genome‐wide CRISPR/Cas9 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Chune Yu et al reported that a genome-wide CRISPR-Cas9 knockdown screen identi ed GRB7 as a driver of MEK inhibitor resistance in KRAS mutant colon cancer [19].Qianqian Wang et al identi ed MDM2 as an essential gene and potential therapeutic target of WT-p53-RTK Non-small cell lung adenocarcinoma(NSCLC) by genome-wide CRISPR/Cas9 screening. RG7388 alone or in combination with pemetrexed resulted in signi cant tumor suppression [20]. Xue Sui et al identi ed a novel cisplatin-resistant esophageal oncogene, ERCC8, based on genome-scale CRISPR/Cas9 screening [21].…”
Section: Discussionmentioning
confidence: 99%
“…Chune Yu et al reported that a genome-wide CRISPR-Cas9 knockdown screen identi ed GRB7 as a driver of MEK inhibitor resistance in KRAS mutant colon cancer [19].Qianqian Wang et al identi ed MDM2 as an essential gene and potential therapeutic target of WT-p53-RTK Non-small cell lung adenocarcinoma(NSCLC) by genome-wide CRISPR/Cas9 screening. RG7388 alone or in combination with pemetrexed resulted in signi cant tumor suppression [20]. Xue Sui et al identi ed a novel cisplatin-resistant esophageal oncogene, ERCC8, based on genome-scale CRISPR/Cas9 screening [21].…”
Section: Discussionmentioning
confidence: 99%
“…Genome‐wide CRISPR knockout screening was performed as described 58,59 . As the GeCKO v2.0 library contains 123411 sgRNAs targeting 19,050 genes, about 1.6 × 10 8 NCI‐H460, A549, and BEAS‐2B cells need to be infected to achieve 300‐fold coverage at a multiplicity of infection of 0.3–0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide CRISPR knockout screening was performed as described. 58,59 As the GeCKO v2.0 library contains 123411 sgRNAs targeting 19,050 genes, about 1.6 × 10 8 NCI-H460, A549, and BEAS-2B cells need to be infected to achieve 300-fold coverage at a multiplicity of infection of 0.3-0.5. Cells were seeded in 12-well plates for 24 h and then infected with lentivirus by centrifuging at 450 g for 2 h at 37 • C in the presence of 8 µg/mL polybrene to increase transduction efficiency.…”
Section: Crispr/cas9 Screening With Lenticrisprv2 Librarymentioning
confidence: 99%
“…Two genome-scale CRISPR/Cas9 screenings were conducted in the wild-type TP53 and RTK-containing cell lines with BEAS-2B cells serving as a control. The results showed that MDM2 was a potential therapeutic target ( Wang et al, 2022 ). A genome-scale screen was used to identify tumor suppressor genes through knockout by CRISPR/Cas9 system.…”
Section: Application Of Crispr Screens In Lung Cancer Treatmentmentioning
confidence: 99%